Toxicity Effect of A Mixture Spiked Pepper (Piper aduncum L.) And Castor Bean (Ricinus communis L.) Against Crocidolomia pavonana F. - Narendra, Nathanael Dimas; Dono, Danar; Meliansyah, Rika (CROPSAVER, 2024)
Crocidolomia pavonana is a cabbage crops pest that cause huge losses for farmers. Spiked pepper (Piper aduncum L.) and castor bean (Ricinus communis L.) extracts are known to be used as botanical insecticides because they have toxic compounds. This study aims to evaluate the toxic effects of a mixture of spiked pepper extract and castor oil as plant based insecticides against C. pavonana larvae and assess the index combination. The study consists of toxicity tests using experimental methods with a Randomized Complete Block Design with six treatments and four replications which were analyzed using analysis of probit regression and followed by an analysis of the mixture properties. Toxicity tests were conducted using a single spiked pepper extract, a single castor oil, and a mixture of spiked pepper extract and castor oil. The concentration of single spiked pepper extract used was 0.15%; 0.27%; 0.51%; 0.94%; 1.75%; and control, then the concentration of castor oil was 0.15%; 0.25%; 0.43%; 0.73%; 1.25%; and control, then the concentration of mixture of spiked pepper extract with castor oil was 0.30%; 0.41%; 0.57%; 0.79%; 1.1%; and control with a ratio 1:1. The results of the toxicity test showed that the mixture of spiked pepper extract with castor oil was toxic with LC50 and LC95 of 0.468% and 1.364% respectively at 10 days after treatment. The results of the mixture properties analysis showed that the mixture between spiked pepper and castor oil was additive at LC50 with a Combination Index value of 0.975 and was weakly synergistic at LC95 with a Combination Index value of 0.524.